FERImage: An interactive program for fractal dimension, dper and dmin calculation - Bianchi, Fernando D. (2001)
A computer program has been written for the determination of the D fractal dimension at low scale, of the dper representative parameter of the periodical region at high scale, and the dmin representative parameter of the minimum elemental cell which is repeated in the periodical structure from the variogram. It carries out the simultaneous obtention of the three previous parameters developed by Bonetto and Ladaga. The program also allows to obtain fractal dimension values from the Fourier power spectrum. FERImage has been developed so that the users could choose the rank where the behavior is fractal, not only in the variogram method but also in the Fourier spectrum method.